Political Parties and Democratic Consolidation in Nigeria’s Fourth Republic: Elite Theory Explanation: Array - Musa, David; Ibietan, Jide; Deinde-Adedeji, Oluwatimilehin (Acta Universitatis Danubius. Relationes Internationales, 2020)
The main objective of this paper is to examine the impact of political parties on democratic consolidation in Nigeria’s Fourth Republic (2010 -2019). Political parties are the engine room of democratic societies and without them; there will be no genuine democracy. The Fourth Republic in Nigeria witnessed revitalised activities of political parties after military interregnum. Democratic consolidation largely depends on the character and conduct of the country’s political parties, and the paper interrogates the extent to which they have shaped or stagnated democracy. This study adopts elite theory as framework, and was predicated on historical design. Data gathered were textually analysed. With a reliance on secondary data such as books, journals and internet materials, the interplay between political parties and democratic consolidation was x-rayed. The challenges to democratic consolidation in the period of study (absence of well-institutionalised political parties, godfatherism, and lack of internal democracy) are observable. This research recommends the overhauling of political parties in order to correct the current state of party politics and democratic practice.